Stabilization of Ribosomal RNA of the Small Subunit by Spermidine in Staphylococcus aureus - Belinite, Margarita; Khusainov, Iskander; Soufari, Heddy; Marzi, Stefano; Romby, Pascale; Yusupov, Marat; Hashem, Yaser (Frontiers in Molecular Biosciences, 2021)
Cryo-electron microscopy is now used as a method of choice in structural biology for studying protein synthesis, a process mediated by the ribosome machinery. In order to achieve high-resolution structures using this approach, one needs to obtain homogeneous and stable samples, which requires optimization of ribosome purification in a species-dependent manner. This is especially critical for the bacterial small ribosomal subunit that tends to be unstable in the absence of ligands. Here, we report a protocol for purification of stable 30S from the Gram-positive bacterium Staphylococcus aureus and its cryo-EM structures: in presence of spermidine at a resolution ranging between 3.4 and 3.6 Å and in its absence at 5.3 Å. Using biochemical characterization and cryo-EM, we demonstrate the importance of spermidine for stabilization of the 30S via preserving favorable conformation of the helix 44.